Freirean Strategies in Meaningful Learning: A Critical Pedagogy of Contextualized Classroom - Khanal, Hota Raj (Journal of Transformative Praxis, 2023)
Employing a qualitative research method and Freire’s critical pedagogy as the main lens, this study explores the techniques of using the contextual approach in the context of secondary-level public schools in Nepal. Critical pedagogy is seen as one of the burning theories to uplift marginalized learners for equity to enhance the quality of education in the field of English language teaching. Contextualized teaching is not a new approach where its usefulness is understood and practiced. And to a lack of training and the traditional teaching model still being dominant, this approach has yet to take traction in many school levels of English teaching in Nepal. Data are obtained from participants' in-depth interviews and written documents which were transcribed and analyzed for developing themes. Teachers who have been teaching for long years at the secondary level applying a contextual approach were purposefully selected as the participants for this study. Through the eyes of the participants, the natural world was seen and reached in the conclusion incorporating the practices and experiences. Based on the perspectives of participants and practices the collected data were interpreted and analyzed. Moreover, my own past experience as a student in a rural public school in Nepal also provides the initial drive for this study. Triangulation of data suggests that contextualizing English language teaching practices exists and exhibits in multiple ways, and they need to be foregrounded for the benefits they have for innovative teaching, organic learning, linking learning with real life and providing students with tools and opportunities to empower themselves as well as own learning.